Security Disturbances in the 2024 Regional Elections in the South Sumatra Regional Police Area of Responsibility - Hendra Pratikno, Muhammad; Zahri, Saifudin; Hasan, KN Sofyan (Universitas Labuhanbatu, 2025)
The importance of democratic life in society supports the creation of a comfortable life together. The Indonesian nation has tried to implement various types of democracy and has also proven the importance of democratic life in society. This makes the implementation of the democratic party which will take place in the 2024 elections the thing that the Indonesian people are most looking forward to. The issues being studied and analyzed are the factors that prevent the National Police Mobile Brigade Unit from responding to serious security disturbances during the 2024 regional elections in the area of responsibility of the South Sumatra Regional Police. The method used is empirical legal research. As a result, the factors that hinder it are law, law enforcement, facilities and infrastructure, and community factors and political culture factorsKeywords: police brigade; security breaches; South Sumatra Regional Police; critical challenges